2015
DOI: 10.4103/0972-124x.145808
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of a 940 nm diode laser as an adjunct in flap surgery for treatment of chronic periodontitis

Abstract: Background:Lasers have several potential benefits such as antibacterial effect and stimulation of wound healing. In addition, hemostasis and delaying epithelial migration may facilitate the outcome of flap surgery. There is a minimal research and evidence currently available for the optimum method of use of a diode laser in flap surgery and its benefit and safety. Hence, this study aimed to investigate the adjunctive effect of diode laser irradiation in open flap debridement (OFD), while treating chronic perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 28 publications
3
21
4
1
Order By: Relevance
“…This is in accordance with another study in which similar results were reported. [ 27 ] However, in contrast to the present study, one study reported significantly less pain experienced by patients in the test sites with a mean score of 2.4 + 1.9 compared to the control sites 3.6 + 2.7 which was attributed to the biostimulation effect of laser. [ 32 ] However, a few studies[ 30 33 ] reported no statistically significant differences in pain scores between the sites.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with another study in which similar results were reported. [ 27 ] However, in contrast to the present study, one study reported significantly less pain experienced by patients in the test sites with a mean score of 2.4 + 1.9 compared to the control sites 3.6 + 2.7 which was attributed to the biostimulation effect of laser. [ 32 ] However, a few studies[ 30 33 ] reported no statistically significant differences in pain scores between the sites.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 26 ] Whereas, in contrast to the present study, one study showed a significant difference between the groups with a greater reduction of gingival inflammation in the laser group which was attributed to the bacterial reduction achieved by the use of laser. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…3 Sample size requirement of split mouth design are much less as compared to other methods. The present study showed that there was no significant difference in the post-operative healing and outcome after gingivectomy with laser or electrocautery.…”
Section: Discussionmentioning
confidence: 98%
“…Plaque index among the two groups showed significant difference indicated that laser groups showed better reduction in PI, indicating the bacterial reduction achieved using laser, as revealed by previous studies evaluated the effect of LLLT on plaque formation (30) . Gingival index' results were significantly different between the groups in favor to laser groups, indicating its greater effect in reduction gingival inflammation.…”
Section: Discussionmentioning
confidence: 55%